2009
DOI: 10.1590/s1516-89132009000600012
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical biomarkers of exposure to deltamethrin in freshwater fish, Ancistrus multispinis

Abstract: This study aimed to determine the effect of sublethal doses of deltamethrin, using biochemical biomarkers as activities of cholinesterase (ChE), ethoxyresorufin-O-deethylase (EROD) and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Similarly reproductive impairment in zebra fish was also reported by Sharma and Ansari (2010). Deltamethrin has also been reported to alter normal ion flux in Ancistrus multifilis (De Assis et al 2009). Further, Gunes and Yeril (2011) noticed that deltamethrin inhibited the lipase activity which has a negative effect on nutrition and physiological condition of fish causing poor reproductive responses in Guppies (Poecilia reticulata).…”
Section: Reproductive Physiology Of Fishessupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly reproductive impairment in zebra fish was also reported by Sharma and Ansari (2010). Deltamethrin has also been reported to alter normal ion flux in Ancistrus multifilis (De Assis et al 2009). Further, Gunes and Yeril (2011) noticed that deltamethrin inhibited the lipase activity which has a negative effect on nutrition and physiological condition of fish causing poor reproductive responses in Guppies (Poecilia reticulata).…”
Section: Reproductive Physiology Of Fishessupporting
confidence: 62%
“…The development of oxidative stress in different fish tissues following deltamethrin exposure has been suggested as the main cause of toxicity (Sayeed et al 2003;Abdollahi et al 2004;Diana et al 2007). Extensive use of deltamethrin may affect the aquatic environment and can kill or at least adversely influence the aquatic life especially fish which are highly sensitive to deltamethrin (De Assis et al 2009;Pimpao et al 2008). Rodrigues (2003) explained the high sensitivity of DM absorption due to lipophilic characteristic even at lower concentration by fish gills as compared to mammals.…”
Section: Deltamethrinmentioning
confidence: 99%
“…The expression of PaCYP4 mRNA showed the inverse time trend, which firstly increased and then decreased gradually with the prolonging DM exposure. It inferred that DM is easily degradated in environment, the reaction to DM exposure in some animals is alleviated with the time prolonging and the result in our study was similar as this phenomenon (Stegeman and Hahn, 1994;Assis et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…EROD activity, a functional and specific assessment of CYP1A1, is highly sensitive as an in vivo bioindicator of exposure to xenobiotic chemicals [22], and has been widely used as a biomarker for monitoring water pollution in aquatic species such as fishes [21,26,27,[35][36][37][38][39][40]. However, few studies have been reported on the activity and induction of CYP1A1 in terrestrial invertebrates such as earthworms [2,16,[41][42][43], among which most failed to detect EROD activity in earthworms [16,41,43], possibly due to three reasons.…”
Section: Discussionmentioning
confidence: 99%